Mitos Keris dalam Novel Hunus Karya Sunaryono Basuki Ks - Dwi Jayanti Putri, Sri Septi; Matildis Banda, Maria; Jumadiah, Sri (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p01, 2018)
The object of this study was the novel Hunus by Sunaryono Basuki Ks. The novel Hunus was analyzed by using theory of structure and theory of literature sociology. The using of theory of literature sociology in this study was proper because the novel Hunus had an intense social depiction of traditional belief about the supernatural power of kris. The problems of study discussed were the structure of the novel and the myth of kris within the aspects of culture, religion, and education that were revealed in the novel Hunus. The structure of the novel Hunus encompassed: plots, characterization, and backgrounds. The plots of the novel Hunus used the plot of mix. The characterization was divided into the main character and the additional characters, the main character was Anthony Wright, and the additional characters were Anak Agung Ngurah Ari Maharani, Wayan, Husni, and Ida Bagus Sudiara. The background of place happened in Jakarta and England, the background of time was in 1990’s, and the background of social told about the life of Balinese people. The myth of kris in the novel Hunus was focused on three aspects; they were the aspects of culture, religion, and education. The aspect of culture discussed about the ceremony of Tumpek Landep. In the novel, it was explained about the procedures of Balinese people in purifying heirlooms, in this case it was kris, on the ceremony of Tumpek Landep. The aspect of religion discussed about the religious background of the characters who believed in the myth of kris. Tony with his personal religious principle considered that the myth of kris was just a fairytale or superstition which only applied to the people who believed it. Meanwhile Gung Ari (Tony’s wife) was Hindu that she believed in the myth of kris from generation to generation in the form of religious advice that had to be believed as customs which had existed in Balinese society. Then, his thought changed when he experienced the spiritual power of kris that "killed" everytime being impaled. Meanwhile Gung Ari (Tony's wife) was Hindu that she believed in the myth of kris from generation to generation in the form of spiritual advice or the ritual of Tumpek Landep that had to be believed . The aspect of education discussed about the education obtained by the religious characters that influenced the perspective towards the myth of kris that happened in the conflict of the novel. Getting the same formal education, but Gung Ari obtained an informal education from her family about the myth of kris. The myth of kris in the novel Hunus taught us that we must respect every faith in a society even though we were not born and grown in the belief of that myth.